Kajian : Pestisida Glifosat (N-phosphonomethyl-glycine) Pada Perkebunan Kelapa Sawit dan Lingkungan Menggunakan Alat Pendekatan PRISMA - Anggraeni, Trisna; Samosir, Rony Harlen; Siahaan, Tria Putra; Pasaribu, Felix Yudha; Sandro, Ales; Haura, Khanaya Balqis; Simarmata, Armando Sahat Parulian; Saragih, Sri Wahyuna; M, Maisarah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The use of pesticides containing the active ingredient Glyphosate (N-phosphonomethyl-glycine) in oil palm plantations has raised concerns about serious environmental impacts. This article aims to analyze the environmental impacts caused by the use of Glyphosate (N-phosphonomethyl-glycine) in oil palm plantations. This article presents a study of the use of the herbicide Glyphosate (N-phosphonomethyl-glycine) with the Preferred Reporting Items for Systematic Reviews and Meta-analysis Item (PRISMA) Approach used to identify, filter, and include relevant articles. Identifying articles related to the use of the active ingredient Glyphosate (N-phosphonomethyl-glycine) in the oil palm plantation sector that meet the requirements for analysis is one of the writing methods. The findings indicate that there are high levels of residues in the use of Glyphosate (N-phosphonomethyl-glycine) in the soil and water around the plantation. The findings show the accumulation of residues of Glyphosate (N-phosphonomethyl-glycine) which is often known by the trade name Roundup which exceeds the safe threshold, has the potential to harm soil and water quality, and affect the growth of oil palm plants themselves. The findings also show that Roundup has an impact on biodiversity around the plantation with a significant decrease in the diversity of flora and fauna. This indicates a negative impact on the local ecosystem. So this article highlights the urgency to implement sustainable pesticide management practices in the oil palm industry. Strengthened environmental protection measures are needed, including monitoring the use of Roundup and developing more environmentally friendly alternatives.